Exposure to violence and its relationship to psychopathology in adolescents. Issue 4 (1st December 2001) - Ward, C L; Flisher, A J; Zissis, C; Muller, M; Lombard, C
Abstract : Objectives —This study aimed to establish prevalence of adolescents' exposure to violence and related symptoms in the South African context and to explore relationships between exposure and symptoms. Setting —Four high schools in Cape Town, South Africa. Methods —Self report questionnaires were administered to 104 students. Types of violence explored included: witnessing or being a victim of violence perpetrated by someone known to the child or in the home and witnessing or being a victim of violence perpetrated by a stranger. The Harvard Trauma Scale, Beck Depression Inventory, and Zung Self-Rating Anxiety Scale were used to assess potentially related symptoms. Results —The majority of children had been exposed to at least one type of violence, and exposure to the one type of violence was related to the other type. Symptoms of post-traumatic stress disorder and depression appear to be related to most types of exposure to violence, but anxiety symptoms only to exposure to violence perpetrated by someone known to the child or in the home. Conclusions —Rates of exposure to violence, and related symptoms, were unacceptably high. Symptoms were associated with exposure to violence.